1993
DOI: 10.1093/oxfordjournals.aje.a116663
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lung Cancer Incidence in the Elderly using Medicare Claims Data

Abstract: The Surveillance, Epidemiology, and End Results (SEER) program of the National Cancer Institute provides data for making national estimates of lung cancer incidence and for monitoring secular trends. The authors compared the number of cases of lung cancer and the incidence rates among elderly residents of the five states included in the SEER program in 1986-1987 with the number of incident cases identified and the rates calculated using hospitalization and enrollment data on elderly Medicare beneficiaries main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Despite the observation that exact values may not match between administrative data and data from other sources, relative differences tend to be highly consistent (e.g. 18,48,67).…”
Section: Geographic Variationmentioning
confidence: 93%
“…Despite the observation that exact values may not match between administrative data and data from other sources, relative differences tend to be highly consistent (e.g. 18,48,67).…”
Section: Geographic Variationmentioning
confidence: 93%
“…Our approach resembles that used by Whittle and coworkers 7 and McBean and coworkers 8 for evaluating the accuracy of Medicare hospitalization data for estimating cancer incidence. In addition, we used other data sources for evaluating the validity of the derived incidence trends.…”
Section: Methodsmentioning
confidence: 99%
“…We included patients if there was one MEDPAR code for cancer of the lung or bronchus or two carrier codes for cancer of the lung or bronchus more than 30 days apart. Several previous studies have shown that lung cancer [16,17] and incident cancer [18] can be identified reliably using Medicare data with specific criteria. We excluded non-US residents and beneficiaries for whom there was any termination of coverage other than for hospice or death.…”
Section: Cohort Assemblymentioning
confidence: 99%